Field Testing of Fence Type Blast Wall for Blast Load Mitigation - Hao, Yifei; Hao, Hong; Shi, Y.; Wang, Z.; Zong, R. (World Scientific Publishing Co. Pte. Ltd., 2017)
To protect structures from external explosions, solid protective barriers have been demonstrated by experimental and numerical studies to be able to effectively mitigate blast loads on structures behind them. However, to protect against blast loads, barriers normally need to be designed to have high structural resistance and ductility. This often requires bulky and heavy protective barriers which are not only highly costly but also often not appropriate for application in downtown areas as they are not friendly to city planning or appearance. Fence type blast wall consisting of structural columns was recently proposed and its effectiveness in mitigating blast loads was investigated through numerical simulations. It was found that the wave–fence interaction and interference of waves significantly reduced the wave energy when the blast wave passed through the fence blast wall. To further investigate the effectiveness and applicability of fence type blast wall as a highly potential technology for structural protection in an urban area, field tests have been conducted and results are reported in this paper. Columns with circular and triangular cross-sections were adopted to build fence blast walls. In addition, a masonry wall was also constructed as solid barrier for comparison. Hemispherical TNT explosive weighing 1.0(Formula presented.)kg with different stand-off distances was detonated on the ground to generate the blast load. Blast overpressures in free air, behind the fence blast wall and behind the masonry wall were recorded by pressure sensors. The effectiveness of the fence blast wall in reducing blast wave and protecting structures was demonstrated by the test data.